Small nucleolar RNAs U32a, U33 and U35a are critical mediators of metabolic stress - Michel, Carlos I. (2011)
Lipotoxicity is a metabolic stress response implicated in the pathogenesis of diabetes complications and has been shown to involve lipid-induced oxidative stress. To elucidate the molecular mechanisms of lipotoxicity, we used retroviral promoter trap mutagenesis to isolate a cell line that is resistant to lipotoxic and oxidative stress. We show that loss of three box C/D small nucleolar RNAs (snoRNAs) encoded in the ribosomal protein L13a (rpL13a) locus is sufficient to confer resistance to lipotoxic and oxidative stress in vitro and prevents the propagation of oxidative stress in vivo. Our results provide evidence for a previously unappreciated, non-canonical role for box C/D snoRNAs as regulators of metabolic stress response pathways in mammalian cells.